Examining knowledge transfer between design research and healthcare design practices: an interpretive comparative case study - Iedema, Alyssa, author; Malinin, Laura, advisor; Kwon, Jain, advisor; Graham, Daniel, committee member (Colorado State University. Libraries, 2023)
The utilization of research to inform design decisions has been a rising topic of discussion. There is a gap between design research, how it is communicated and its accessibility, and the design industry, the ones responsible for designing and building the environments people inhabit (Huber, 2017). There have been few studies investigating how interior design practitioners are acquiring and applying research to inform their design decisions (e.g., Dickson and White, 1993; Huber, 2016b; 2017). Architecture and design firms have started to invest in developing in-house research labs in attempt to bridge the gap (Donofrio, 2013; Huber, 2016a). The purpose of this comparative case study is to explore how architecture and design firms in the United States are engaging with design research throughout the design process, including if and how engagement differs between firms with in-house research labs and those without. A total of 8 firms were studied (4 of these had in-house research labs). A content analysis of each firm's website was conducted to understand how they are describing their engagement with research to find essential themes across cases. Ten individuals, consisting of interior design practitioners and design researchers, were then interviewed to gain an understanding of research utilization from their perspective. Findings suggest that eight themes in which research is involved in the design process: 1) motivation for research 2) definition of research 3) organization of research 4) identifying knowledge 5) selecting knowledge 6) adapting knowledge 7) implementing knowledge 8) disseminating knowledge. Findings also suggest that there is an inconsistent communication and expectation of research across all firms.
Keywords: design research; interior design; research utilization; healthcare design; case study; knowledge translation